Places and spaces in the weightless economy - Huiwen Gong (Philipps-University Marburg, Department of Geography, 2016)
Proposition of the 'end of geography' based on globalization and digitalization has been heavily criticized by different geographers in the last decades. This paper mainly focuses on the digitalization side of debate because of the more obvious and contradictory relationships between geography and digital production/consumption. Based on a systemic reflection on the literature in new media industry in general, and video game industry in particular, this paper bridges two different strings of research in the weightless economy. By referring to previous respondents' opinions as well as extracting new ideas from other empirical studies, this paper organizes its arguments in a comprehensive way and supports these arguments with abundant empirical evidence found in different case studies. It contributes to economic geographers' side of debate on the role of geography in today's weightless economy.
Keywords: A14; D20; 330; the weightless economy; the end of geography; new media; video game industry